2010
DOI: 10.1038/nrneurol.2010.89
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as a metabolic link to multiple sclerosis

Abstract: Clinical and experimental data, together with epidemiological studies, have suggested that the pathogenesis of multiple sclerosis (MS) might involve factors that link the immune system with metabolic status. Moreover, recent research has shown that leptin, the adipocyte-derived hormone that controls food intake and metabolism, can promote experimental autoimmune encephalomyelitis, an animal model of MS. In patients with MS, the association of leptin with disease activity has been dissected at the molecular lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 45 publications
1
90
0
2
Order By: Relevance
“…Previous studies have shown that MS is associated with increased levels of leptin in serum and cerebrospinal fluid (CSF) specimen drawn from naive-to-treatment relapsing-remitting MS (RRMS) patients in the acute phase of their disease [16,17,18]. Higher serum levels of leptin were also found in patients with MS in remission, as compared with healthy controls [19].…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have shown that MS is associated with increased levels of leptin in serum and cerebrospinal fluid (CSF) specimen drawn from naive-to-treatment relapsing-remitting MS (RRMS) patients in the acute phase of their disease [16,17,18]. Higher serum levels of leptin were also found in patients with MS in remission, as compared with healthy controls [19].…”
Section: Introductionmentioning
confidence: 88%
“…In conclusion, the results reported in this study may facilitate a better understanding of the role of ECs and CB 1 receptors in leptin-mediated effects on food intake and energy storage/expenditure as well as other physiopathological functions of this hormone, such as its role in neuroinflammation (38).…”
Section: -Agmentioning
confidence: 99%
“…Normal leptin levels crucially maintain and regulate the body's immune function. Emerging evidence indicates that leptin acts as a proinflammatory cytokine in immune responses such as systemic lupus erythematosus (SLE) [3][4][5][6], RA [7][8][9][10], multiple sclerosis (MS) [11][12][13] and psoriasis [14][15][16]. Leptin could be a member of the cytokine network managing the inflammatory immune response and host defence mechanisms.…”
Section: Introductionmentioning
confidence: 99%